Identification and Characterization of Two Novel RNA Editing Sites in grin1b Transcripts of Embryonic Danio rerio - Pedro Pozo; Barry Hoopengardner (Neural Plasticity)
Discovering RNA editing sites in model organisms provides an insight into their adaptations in addition to finding potential sites for the regulation of neural activity and the basis of integrated models of metazoan editing with a variety of applications, including potential clinical treatments of neural dysregulation. The zebrafish, Danio rerio, is an important vertebrate model system. We focused on the grin1b gene of zebrafish due to its important function in the nervous tissue as a glutamate receptor. Using a comparative sequence-based approach, we located possible RNA editing events within the grin1b transcript. Surprisingly, sequence analysis also revealed a new editing site which was not predicted by the comparative approach. We here report the discovery of two novel RNA editing events in grin1b transcripts of embryonic zebrafish. The frequency of these editing events and their locations within the grin1b transcript are also described.